2019
DOI: 10.1152/ajpheart.00342.2018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of growth differentiation factor 11 on autophagy deficiency-induced dedifferentiation of arterial smooth muscle cells

Abstract: Growth differentiation factor (GDF)11 has been reported to reverse age-related cardiac hypertrophy in mice and cause youthful regeneration of cardiomyocytes. The present study attempted to test a hypothesis that GDF11 counteracts the pathologic dedifferentiation of mouse carotid arterial smooth muscle cells (CASMCs) due to deficient autophagy. By real-time RT-PCR and Western blot analysis, exogenously administrated GDF11 was found to promote CASMC differentiation with increased expression of various differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In our animal studies, we examined whether AC deficiency in the endothelium could augment the release of IL-1β-containing EVs into the arterial wall that contribute to hypercholesterolemia-induced vascular remodeling. Our previous studies have demonstrated that in the PLCA model, hypercholesterolemic injury by WD promotes VSMC dedifferentiation into synthetic phenotypes, leading to VSMC proliferation and migration, which are essential to the development of neointima ( Yuan et al, 2018a ; Yuan et al, 2019a ). To this end, we generated endothelium-specific AC gene knockout mice (Asah1 fl/fl /EC cre ) and used these mice and their WT littermates to produce the PLCA model with ND or WD.…”
Section: Discussionmentioning
confidence: 99%
“…In our animal studies, we examined whether AC deficiency in the endothelium could augment the release of IL-1β-containing EVs into the arterial wall that contribute to hypercholesterolemia-induced vascular remodeling. Our previous studies have demonstrated that in the PLCA model, hypercholesterolemic injury by WD promotes VSMC dedifferentiation into synthetic phenotypes, leading to VSMC proliferation and migration, which are essential to the development of neointima ( Yuan et al, 2018a ; Yuan et al, 2019a ). To this end, we generated endothelium-specific AC gene knockout mice (Asah1 fl/fl /EC cre ) and used these mice and their WT littermates to produce the PLCA model with ND or WD.…”
Section: Discussionmentioning
confidence: 99%
“…β‐Actin was used as internal control to normalize the expression of mRNA. Fold changes were calculated as follows: 2 −ΔΔ threshold cycle …”
Section: Methodsmentioning
confidence: 99%
“…β-Actin was used as an internal control to normalize the expression of mRNA. Fold changes were calculated as follows: 2 −∆∆ threshold cycle [74].…”
Section: Real Time-pcr Studiesmentioning
confidence: 99%